Revista digital del barrio tradicional “La Tola”, ubicado en el centro de Quito. - Jiménez Chalán, David Andrés (2017)
The visual narrative with respect to the generation of meaning, has a close relationship with the handling and treatment of the information sought to be transmitted. For that reason the elaboration of the “Revista sobre memoria y tradición, Barrio La Tola” constituted a complex exercise at the moment of expressing the historical memory of a traditional sector like "The Tola". It was vital to manage life stories to create a striking communicational product, with the advantages of digital. The photographs used as content of this magazine allow us to visualize the evolution of the traditional neighborhood "La Tola", in this way the message shows the changes that the sector has experienced in the last decade, which in turn will strengthen the link with the inhabitants of Quito today. The image allows to capture reality and makes photography a substantial tool to demonstrate the relationship of the neighborhood "La Tola" with its inhabitants and the Quito citizenship, which is shown along with the historical evolution of this traditional place, to make visible its customs and traditions, endowing the magazine with an identity character, of social importance for the residents.